Web-assisted living diversity digital teaching materials to improve students' science literacy and environmental attitudes - Megah Sri Retno Apriliana; Fatchur Rohman; S. Suhadi (Universitas Muhammadiyah Malang, 2024)
The 21st century skills measured at Senior High School 9 Malang are communication, collaboration, critical thinking, and creativity, while science literacy and environmental attitudes have never been measured before. This study aims to improve students' science literacy and environmental attitudes in a valid, practical, and effective way. The research and development model refers to Lee and Owens, which was implemented in Grade X Senior High School 9 Malang with a sample size of 34 people. The developed teaching materials were tested for validity, practicality, and effectiveness. In addition to expert validation tests, empirical validity tests were also carried out using Pearson product moment and reliability using Cronbach's alpha. The results obtained from the development of web-assisted digital teaching materials on the diversity of living things are valid, practical, and effective. The empirical validity value using Pearson's product moment obtained significance <0.05, so that the valid criteria were obtained, and the reliability value of Cronbach's alpha obtained 775 reliable categories. The effectiveness test results using N-gain obtained a value of 0.43 in the moderate category.